Compliance with the Principle of Non Bis in Idem in Criminal Proceedings Regarding Domestic Violence - V. H. Drozd; V. V. Ablamska (Bulletin of Kharkiv National University of Internal Affairs)
The article analyses the legal mechanism for compliance with the principle of non bis in idem in criminal proceedings regarding domestic violence. It is emphasised that compliance with the principle of non bis in idem during the pre-trial investigation of criminal offences under Article 126-1 of the Criminal Code of Ukraine is important in terms of both ensuring human rights and bringing a person to criminal responsibility in proportion to their guilt. A comparative analysis of the normative consolidation of the non bis in idem principle in national and international legislation has been conducted. The main conditions for compliance with the non bis in idem principle in criminal proceedings concerning domestic violence have been identified. It is emphasised that important factors in complying with the non bis in idem principle in criminal proceedings regarding domestic violence are not bringing a person to justice twice for the same acts, which are initially classified as administrative offences and then as criminal offences. However, the previous bringing of a person to administrative responsibility for committing domestic violence, provided that the unlawful actions are repeated and specific consequences more serious than those specified in the legislation of Ukraine on administrative offences occur, does not indicate double legal liability of one type for the same offence, but confirms the systematic nature of the actions of the guilty person. It has been established that in criminal proceedings regarding domestic violence, in order to comply with the principle of non bis in idem in the event of competing criminal law provisions, each of which covers a separate criminal offence, if the offence is simultaneously covered by general and special provisions, then there is no combination of criminal offences, and the special provision that best reflects the specifics and characteristics of such a socially dangerous act shall be applied.